Alternative techniques of estimating import demand elasticities - Mcaleese, D (Economic & Social Studies, 1970)
The desirability as well as the difficulty of obtaining reliable estimates of import demand elasticities is clearly demonstrated by the extensive literature on the subject during the last few decades. Interest in price elasticities of import demand originated in Marshall's discussion of the possibility of a devaluation causing a deterioration rather than an improvement in the balance of payments. Since then, the use of price elasticities in theoretical and empirical work has become widespread. Price elasticities have, for example, been employed extensively in analysing the effects of tariff elimination within the EEC and the effect of the 'Kennedy round' tariff reductions on world trade patterns. Income/output elasticities of import demand are also exceedingly useful tools. For example, they enable us to assess the implications for total import demand of different projected growth rates o f gross national product (GNP). The estimation of import demand elasticities is thus a matter o f considerable importance for economic policy.
Keywords: Economics; Sociology